Unlocking insights: Malaysian teen perspectives on modern smartphone design trends / Nur Hasni Nasrudin ... [et al.] - Nasrudin, Nur Hasni; Ahmad, Nahdatul Akma; Ahmad, Samsiah; Ahmad Salleh, Khairulliza; Ahmad Junid, Rosida (UiTM Cawangan Perlis, 2024)
This study investigates the complex realm of modern smartphone design through the lens of Malaysian teenagers, aiming to uncover significant insights into their preferences and viewpoints. Understanding the way teenagers perceive and interact with smartphones remains crucial, despite the ubiquity of these devices in today’s digital society. This research addresses a notable gap in the existing literature by specifically examining the perspectives of Asian individuals, particularly Malaysian teenagers. It aims to shed light on their unique cultural backgrounds and technological inclinations. A meticulously organised workshop was conducted, involving ten teenagers from Perak State, Malaysia. The participants engaged in talks and creative exercises, delving into different facets of smartphone design elements and applications. The research identifies five key areas to consider when designing smartphones: the physical shape and materials used, the type of display technology employed, the security measures and user identification methods, the audio and multimedia capabilities, and the networking options and charging mechanisms. Additionally, there are three themes that can be used to customise the features of smartphone applications to meet the requirements of teenagers: security and authentication, productivity and creativity tools, and cutting-edge features and technologies. This project aims to develop culturally responsive and user-friendly smartphone designs, enhancing user experiences by bridging global technological trends with local consumer behaviours.